The Integration of Strategic Intelligence and Cyber Resilience in Combating Organized Narcotics Crime in Indonesia (A Case Study of Hydra Indonesia) - Aziz, Wawan Kurniawan; Daryanto, Eko (Security Intelligence Terrorism Journal (SITJ), 2025)
Organized Narcotics Crime in Indonesia is evolving through the utilization of technologies such as the dark web, encrypted communications, and cryptocurrency transactions. The Hydra Indonesia case, uncovered in Bali in 2024, illustrates how international narcotics syndicates leverage cyber technology to evade law enforcement detection and expand their operations. This article examines the integration of strategic intelligence and cyber resilience as effective measures to address these threats. The findings of this discussion highlight that the synergy between strategic intelligence and cyber resilience plays a critical role in early detection, criminal network mapping, and enhanced coordination among law enforcement agencies. This integration optimizes technological resources for more effective prevention and enforcement efforts against organized narcotics crime. Policy recommendations include strengthening cyberinfrastructure, enhancing intelligence capacity, and fostering international collaboration to reinforce the national response to narcotics crime threats in an increasingly complex and global digital era.